The role of glycogen synthase kinase 3β in adhesion-dependent survival signalling in human oesophageal squamous cell carcinoma - Crooks, Lauren (My University, 2020)
Glycogen synthase kinase 3β (GSK3β) has been shown to have more predicted substrates than any other kinase, and thus is suggested to be involved in the regulation of almost every cellular process, however; the interrelationship between GSK3β and its interactors in signalling pathways remains poorly elucidated. Unsurprisingly, dysregulation of GSK3β has been observed in a number of pathological conditions, including cancer. Interestingly, GSK3β is constitutively active under normal conditions, but phosphorylation at Ser-9 leads to inhibition of its activity. The regulation of GSK3β appears complex, and its role in cancer cell survival appears contradictory. This research investigates the role of GSK3β in survival signalling in human oesophageal squamous cell carcinoma (HOSCC), and elucidated that both inactive and active phosphorylated forms are present and differentially regulated. However, it was found that the inactive form of GSK3β contributed notably to enhanced cancer cell survival through diminishing cleaved caspase 3, the executioner caspase of cell death in the form of apoptosis. Furthermore, inactive GSK3β increased proliferation and viability in HOSCC, suggesting inactive GSK3β may be critical in facilitating selective growth advantages in HOSCC. In addition to observing the role of GSK3β on intracellular signalling, the role of GSK3β on adhesion-mediated communication was elucidated. HOSCC appear highly dependent on a dynamic extracellular environment, therefore communication between the cancer cell and surrounding extracellular matrix (ECM) remains indispensible to the progression of the disease. It was found that β1 integrin receptors are present at high levels in HOSCC and are positively regulated by inactive GSK3β. Consequently, a signalling axis between β1 integrin receptors and GSK3β exists in HOSCC and functions in the maintenance of survival and the highly aggressive nature of the malignancy.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science in Molecular and Cell Biology, Faculty of Science, University of the Witwatersrand, Johannesburg, 2020